(untitled) (Research, Society and Development, 2020)
Drug delivery systems are constantly evolving and developing, as well as the search for promising and effective formulations for drug delivery. Computational simulation methods enable the development of complex systems, such as nanostructured lipid carriers (NLC), the understanding of interaction and dynamics between drug molecule and its transporter. In this work, aimed to simulate a NLC containing cupuassu fat triacylglycerols, carnauba wax and caprylic/capric acid triacylglycerol, stabilized with Tween 80 and Pluronic and ketoconazole enantiomer as drug was simulated. Initially, lipid mixtures were studied by Differential Scanning Calorimetry and X-ray diffraction. Subsequently, computational studies were carried out, among which Molecular Docking of ketoconazole to the lipid mixture and Molecular Dynamics of NLC system containing ketoconazole. From the results obtained it was possible to observe the main binding affinities of the drug and provide a better NLC formulation. It was also possible to propose a three-dimensional NLC model that was stable after molecular dynamics and ideal for future experimental studies.